Relationships among Parent-child Communication, Self-esteem and Sexual Assertiveness for Male and Female University Students: Gender Difference - Bo Mi Kim; Jung Suk Park (Korean Society of Women Health Nursing, 2015)
PURPOSE: The purpose of this study was to compare the relationships among parent-child communication, self-esteem and sexual assertiveness for male and female university students. METHODS: This descriptive study used a comparative survey design that utilized self-report questionnaires. A total of 470 participants were male and female university students in B metropolitan city. RESULTS: The degree of open communication use was higher for female students in comparison to male students, There were no differences in dysfunctional communication for both the father-child communication. There were no differences between males and females for the mother-child communication either. The degree of self-esteem was higher for male students in comparison to the female students. The degree of sexual assertiveness was higher for female students in comparison to the male students. The grade, religion, major, allowance source, marital status of parents, and relationship experience with opposite sex were influencing factors for the male students' sexual assertiveness whereas the individual's major and physical contact were influencing factors for the female students. CONCLUSION: Self-esteem and mother-child open communication were influencing factors of sexual assertiveness. Thus, the nursing intervention based on the influencing factors is needed in order for male and female students to express sexual assertiveness.